Long-term modulation of A-type K(+) conductances in hippocampal CA1 interneurons in rats after chronic intermittent ethanol exposure during adolescence or adulthood - Li, Qiang (2013)
BACKGROUND: Chronic alcohol use, especially exposure to alcohol during adolescence or young adulthood, is closely associated with cognitive deficits that may persist into adulthood. Therefore, it is essential to identify possible neuronal mechanisms underlying the observed deficits in learning and memory. Hippocampal interneurons play a pivotal role in regulating hippocampus-dependent learning and memory by exerting strong inhibition on excitatory pyramidal cells. The function of these interneurons is regulated not only by synaptic inputs from other types of neurons, but is also precisely governed by their own intrinsic membrane ionic conductances. The voltage-gated A-type potassium channel (I(A)) regulates the intrinsic membrane properties of neurons, and disruption of I(A) is responsible for many neuropathological processes including learning and memory deficits. Thus, it represents a previously unexplored cellular mechanism whereby chronic ethanol may alter hippocampal memory-related functioning. METHODS: Using whole cell electrophysiological recording methods we investigated the enduring effects of chronic intermittent ethanol exposure (CIE) during adolescence or adulthood on I(A) in rat CA1 interneurons. RESULTS: We found that the mean peak amplitude of I(A) was significantly reduced after CIE in either adolescence or adulthood, but I(A) density was attenuated after CIE in adolescence but not after CIE in adulthood. In addition, the voltage dependent steady-state activation and inactivation of I(A) were altered in interneurons after CIE. CONCLUSIONS: These findings suggest that CIE can cause long-term changes in I(A) channels in interneurons and thus may alter their inhibitory influences on memory-related local hippocampal circuits, which could be, in turn, responsible for learning and memory impairments observed after chronic ethanol exposure.